Phytosociological Survey of Sugarcane Crop Weeds in Different Agroecological Areas in Tucumán Province, Argentina - Cabrera, Debora Carina (2019)
Weeds constitute the main constraint on the productivity of sugarcane agroecosystems in Argentina. This work aimed to analyze the floristic and phytosociological composition of sugarcane weed communities in different agroecological areas in Tucumán. Fifteen plots from each area were sampled 60 to 90 days after crop shooting, by throwing a 0.5 m x 0.5 m quadrat metallic frame six times in random directions in each of the plots. Species found within the frame were identified. Later, fresh and dry biomass weight were calculated per quadrat sample and species. Frequency, density, dominance, importance value index, Shannon-Wiener and Simpson species diversity index and Jaccard similarity index were calculated. The unweighted pair group method with arithmetic mean (UPGMA) was used to interpret similarity. Overall, 35 species were identified, 24 of which were dicotyledons and 11 monocotyledons. Eighteen of them were annual species, versus 17 which were perennial. Considering IVI, the most outstanding families were Poaceae, Cyperaceae, Euphorbiaceae, Amaranthaceae and Asteraceae. The results obtained in all the areas revealed the importance of the species Panicum maximum, Sorghum halepense, Cyperus rotundus, Cynodon dactylon and Euphorbia hyssopifolia. The areas with greater and less diversity were the Depressed Plain-Non-Saline Depressed Plain Subregion and the Subhumid-Humid Chaco-Pampean Plain, respectively. There was a 53% similarity between the Depressed Plain-Saline Depressed Plain and the Depressed Plain-Non-Saline Depressed Plain, and a 47% similarity between the Humid and Perhumid Foothills and the Subhumid-Humid Chaco-Pampean Plain. Hierarchical clustering and Jaccard index led to similar results.